2023
DOI: 10.1001/jamanetworkopen.2023.30885
|View full text |Cite
|
Sign up to set email alerts
|

Gout Flares and Mortality After Sodium-Glucose Cotransporter-2 Inhibitor Treatment for Gout and Type 2 Diabetes

Jie Wei,
Hyon K. Choi,
Nicola Dalbeth
et al.

Abstract: ImportanceRecurrent flares are the hallmark of clinical manifestation of gout. Sodium-glucose cotransporter-2 inhibitors (SGLT2i) have been associated with a lower risk of incident gout; however, their association with recurrent flares is unknown.ObjectiveTo examine the association of SGLT2i vs active comparators (ie, glucagonlike peptide-1 receptor agonists [GLP-1 RA] or dipeptidyl peptidase-4 inhibitors [DPP-4i]) with the risk of recurrent gout flares and all-cause mortality among patients with gout and type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The study utilized a baseline population characterized as having T2D and gout and then given either SGLT2is or comparators (e.g., GPL inhibitor). The study found that the gout patients given the SGLT2is had significantly fewer gout flares and significantly lower all causal mortality [7]. Both studies critically corroborated the link between tubular glucose and increased uric acid excretion by the kidney The potential benefits of SGLT2i for patients with gout has been recently reviewed [84].…”
Section: Sglt2 Inhibitors and Goutmentioning
confidence: 87%
See 1 more Smart Citation
“…The study utilized a baseline population characterized as having T2D and gout and then given either SGLT2is or comparators (e.g., GPL inhibitor). The study found that the gout patients given the SGLT2is had significantly fewer gout flares and significantly lower all causal mortality [7]. Both studies critically corroborated the link between tubular glucose and increased uric acid excretion by the kidney The potential benefits of SGLT2i for patients with gout has been recently reviewed [84].…”
Section: Sglt2 Inhibitors and Goutmentioning
confidence: 87%
“…These include improved cardiovascular and renal functions, an improved lipid profile, weight loss, and uric acid (primarily urate at physiological pH)-lowering effects [4][5][6]. The unexpected increase in urate excretion resulting from SGLT2i use suggests a significant potential benefit to those with hyperuricemia and urate pathologies [7] and highlights the need to better understand the well-known but unresolved relationship between urate levels and metabolic disorders, mainly in T2D.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard prescribers need to consider whether the medications used to manage these comorbidities influence the treatment of gout and vice versa. For example, there is emerging evidence that low‐dose colchicine may be beneficial in reducing cardiovascular events and that sodium‐glucose cotransporter 2 inhibitors lower the risk of recurrent gout flares and mortality in people with gout and type 2 diabetes 24 …”
Section: Managementmentioning
confidence: 99%
“…Post hoc analyses of CVOT data and real-world studies have revealed that the use of SGLT2i therapy is associated with lower serum urate levels and reduced incidence of gout [ 115 119 ]. In addition, a recent cohort study indicated that people T2DM and gout were at lower risk of recurrent gout flares and mortality if they were treated with an SGLT2i, compared with other oral glucose-lowering therapies [ 120 ].…”
Section: A Step-change In T2dm Management: Bridging the Gap Between G...mentioning
confidence: 99%